Fatores críticos na promoção do sucesso escolar de crianças e jovens em acolhimento institucional: Contributos relevantes a partir da investigação - Trigo, Luísa Ribeiro (2016)
Recent international studies have shown that children and young people in out of home care have poorer educational outcomes when compared with their non-care peers. In-care population has been associated to poorer academic performance, school, failure, lower educational attainment, and school instability. In Portugal, as in other European countries, a large number of children and adolescents – more than 8000 – are brought up in residential care settings. Although Portuguese research about educational engagement and outcomes of children in care is still limited, the same worrying educational scenario can be observed. This paper presents a reflection on critical factors in promoting educational success of children and young people in residential care, based on studies conducted in Portugal since 2012. Data highlight the need to provide additional support to these children and adolescents in the academic domain, developing interventions that assume the focus on this dimension and supporting young people in their processes of educational decision making. It is therefore necessary to promote changes in beliefs, attitudes, priorities, and practices.